Self-Recognition Before a Screen-Mirror Between 15 Months and 6 Years, The Contribution of Eye-Tracking and a New Protocol. Issue 3 (27th May 2022) - Luxembourger, Christophe; Fischer, Jean-Paul; Tazouti, Youssef
ABSTRACT: A live video was used to study the development of visual self-recognition in a cross-sectional sample of 152 typically developing French children aged between 15 months to 6 years. Three reactions to a mark placed on the child's cheek without their knowledge were studied: the touch of the mark with their hand, the ocular responsiveness to the mark they discovered on through the screen and, finally, their behavior when the experimenter silently unostentatiously proffered them a tissue. It was mainly shown that (1) the behavior of touching the mark increases until age 3 years, and then declines gradually, (2) from the age of 3, all children spot the mark within the first four seconds, and (3) the behavior of making use of the tissue to wipe the mark increases continuously, particularly from age 3. The latter behavior reveals a superior level of self-awareness: the emergence of a meta-consciousness of oneself.